Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien - Langi, Steven; Winarti, Eko (Jurnal Ilmu Medis Indonesia, 2023)
Purpose: Patient satisfaction is a key indicator of the quality and effectiveness of healthcare services provided by primary health centers and Puskesmas. It is widely acknowledged that the quality of health care services has a direct impact on patients. This literature review aimed to explore the relationship between the quality of healthcare services provided by Puskesmas and patient satisfaction. Methodology: This review analyzed several studies conducted by various researchers, which consistently indicated that good quality services at Puskesmas are positively associated with higher levels of patient satisfaction, whereas poor quality services have a negative impact on patient satisfaction. Result: Effective health service delivery plays a crucial role in meeting the evolving needs and expectations of patients. The review emphasized that patient satisfaction is not solely determined by the performance of healthcare services or meeting standard indicators, but also by the patient's perspective and assessment of their overall experience. Limitations: The review concluded that prioritizing the quality of healthcare services provided by Puskesmas is essential for achieving high levels of patient satisfaction Contribution: The review highlighted the importance of delivering high-quality healthcare services in Puskesmas to ensure patient satisfaction.